PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR FIKIH - Ida Apipah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2019)
This study aims to improve the learning outcomes students on the Jurisprudence Subjects on the Hajj and Umrah material. The research method used was classroom action research conducted in two cycles, each cycle carried out in two meetings. Each meeting consists of planning, action, observation and reflection. The subjects in this study were all students of class X IPS-5 MAN 2, Bandung City in the even semester of the 2016/2017 academic year, totaling 35 students. Data obtained in this study include: learning outcomes and student learning completeness taken from the provision of test questions at each end of the meeting and the activeness of students in the learning process takes place. The results showed the use of a jigsaw cooperative learning model for each cycle obtained an increase. The research data obtained the average learning outcomes in the first cycle was 78.57 and the second cycle was 96.00. The average learning completeness in the first cycle was 74.29% and the second cycle was 100%. Based on these data from cycle I to cycle II there was a significant increase. This means that the use of a jigsaw cooperative learning model can improve the learning outcomes of students of class X IPS-5 MAN 2 Bandung in the Subjects of Jurisprudence on the subject of Hajj and Umrah.